Rekonstruksi Ushul Fiqh Dalam Pemikiran Mohammad Hashim Kamali: Sebuah Kajian Metodologi Hukum Islam Kontemporer : Reconstruction Of Ushul Fiqh In The Thought Of Mohammad Hashim Kamali: A Study Of Contemporary Islamic Legal Methodology - Janah, Sidanatul; Sovia, Sheyla Nichlatus (OBHE: Jurnal Pascasarjana IAIN Papua, 2026)
This research examines the methodological reconstruction of Islamic jurisprudence (ushul fiqh) in the thought of Mohammad Hashim Kamali as a response to the crisis in the relevance of Islamic law in the modern era. Kamali believes that classical Islamic jurisprudence overemphasizes the textual-deductive aspect, thereby neglecting rationality and social context. Through an epistemological synthesis of revelation, reason, and social reality, Kamali offers a model of reconstructive jurisprudence that places the maqashid al-shari’ah and maslahah as the rational foundation of Islamic law. His approach transitioned the legal paradigm from qawli to manhaji, conceptualizing ijtihad as a creative and collective process (ijtihad jama'i) that is responsive to social change. This research uses a qualitative method with a literature review approach, analyzing Kamali's main works such as Principles of Islamic Jurisprudence and Syari’ah Law: An Introduction. The study results indicate that Kamali repositions ushul fiqh as an integrative epistemological system oriented toward justice, freedom, and universal benefit. His contribution lies not only in revitalizing Islamic legal methodology but also in his efforts to build a bridge between normative traditions and the demands of modernity. This finding opens up opportunities for further research to integrate Kamali's rational framework with Jasser Auda's systemic maqashid approach to strengthen the paradigm of Islamic law to be more adaptable to the complexities of contemporary social, technological, and bioethical issues. Thus, Kamali's thinking marks an important phase in the transformation of Islamic legal epistemology toward an ethical, rational, and contextual legal system.